43. TCP approach to predict the pathological response based on MRI-based quantification of early tumor regression in rectal cancer neo-adjuvant radio-chemotherapy. (December 2018) - Fiorino, C.; Gumina, C.; Passoni, P.; Palmisano, A.; Broggi, S.; Cattaneo, G.M.; Di Chiara, A.; Mori, M.; Raso, R.; Slim, N.; De Cobelli, F.; Calandrino, R.; et al.
Abstract : Purpose: Predictive models based on tumor regression represent a promising field of investigation in neo-adjuvant radio-chemotherapy (RCT) of rectal cancer (Rca). The aim of this study was to introduce a radiobiological index based on early tumor regression and to test its ability in predicting the tumor pathological response (pR). Methods: Seventy-four patients were treated in the period 2009–2016 with Helical Tomotherapy (HT) following an adaptive (ART) protocol (41.4 Gy/18fr, 2.3 Gy/fr, concomitant boost on the residual tumor (GTV) in the last 6 fractions, GTV dose:45.6 Gy). Chemotherapy consisted of oxaliplatin on days −14, 0 (HT start), +14 and 5-fluorouracil from −14 to HT end. High resolution T2-weighted MRI were taken before ( MRI pre ) and at half ( MRI half ) HT and GTVs ( V pre, V half ) contoured by a single observer. Based on the Poisson TCP formula, assuming volume regression proportional to the fraction of killed cells (neglecting inter-patient variability of removal kinetic), the "Early Regression Index" ERI TCP = - ln [ 1 - ( V half / V pre ) Vpre ] was introduced. Its discriminative power was assessed by ROC curves (AUC, sensitivity/specificity, positive/negative predictive value (PPV/NPV)); three end-points were considered: pathological complete response (pCR); pCR or clinical complete response without surgery (cCR); limited response (residual vital cells (RVC) in the surgical specimen >10%). Results: Complete data were available for 65 patients: pCR, pCR + cCR and RVC > 10% were 20, 21 and 19. The discriminative power of ERI TCP was moderately high with AUC = 0.79 (95% CI:0.67–0.89), 0.81 (0.69–0.89) and 0.75 (0.62–0.84) for pCR, pCR + cCR and RVC > 10% respectively (p < 0.0005). ERI TCP was highly sensitive (85–90%) with high NPV (90–94%) for all end-points. Fig. 1 shows the relationship between ERI TCP and the probability of pCR + cCR (logistic regression, p < 0.0001, H&L test:0.71): the true rates are also shown, grouped by quartiles. Conclusions: A radiobiologically consistent index based on early regression showed high NPV in predicting pR after ART in neo-adjuvant RCT for Rca, with relevant potentialities for ART/treatment customization.